Students' Perceptions and Performance on ODL Implementation in Computer Programming Course During Covid-19 Pandemic - Abidin, Husna Zainol; Mazalan, Lucyantie; Abdul Aziz, Mohd Azri; Che Abdullah, Syahrul Afzal; Ruslan, Fazlina Ahmat (Journal of Engineering Education Transformations, 2025)
This paper assesses students’ perceptions and performance in Computer Programming (ECE431) course offered in the Universiti Teknologi MARA (UiTM) Malaysia, using Online Distance Learning (ODL) as a new delivery method during Covid-19 pandemic. ODL was conducted beginning Week 5 of the semester, hence there is a need to investigate the students’ acceptance and performance. 53 second year Electrical Engineering undergraduates participated in the assessment. The student's acceptance on the ODL approach was evaluated twice through survey while the performance of the students was evaluated based on Course Outcome (COs) attainment and student's grade. Approximately 50% of the students were struggling to adapt to ODL during initial stage. The percentage of students adapting to ODL increased to nearly 80% at the end of the semester as they have familiarized with the delivery method. Average score for COs attainment and students’ grade were compared with face-to-face classes. The results showed a 24.1% improvement in CO1, as evaluated from quizzes and assignments, as well as reductions in CO2 by 2.6% and CO3 by 11.7% through miniprojects. This is attributed to the programming skills as they are away from lecturers and classmates, which often guide them on miniproject's codes. This study suggests that the changes of teaching and learning approach to ODL did not affect the students’ performance.